2009
DOI: 10.1111/j.1440-1843.2008.01449.x
|View full text |Cite
|
Sign up to set email alerts
|

Non‐invasive ventilation during arm exercise and ground walking in patients with chronic hypercapnic respiratory failure

Abstract: NIV during UAE increased endurance time and reduced dyspnoea compared with exercise without NIV in patients with chronic HRF. Investigation of the role of NIV as an adjunct to UAE training is warranted. In contrast, NIV during ground walking did not improve exercise capacity. However, the pressure support provided may have been inadequate as dyspnoea was not reduced.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(41 citation statements)
references
References 28 publications
0
40
0
1
Order By: Relevance
“…Isotime comparisons are also responsive outcomes of interventions directed to train arm muscles [134][135][136].…”
Section: Evaluativementioning
confidence: 99%
“…Isotime comparisons are also responsive outcomes of interventions directed to train arm muscles [134][135][136].…”
Section: Evaluativementioning
confidence: 99%
“…As many chest wall muscles that are involved in the performance of upper-limb activities also et al [32] similarly found a small but signifi cant improvement in Sp,O 2 at rest and at isotime exercise with NIV plus supplemental oxygen compared with supplemental oxygen alone during ground walking. However, despite the improvement in gas exchange, exercise capacity was not improved.…”
Section: Upper-limb Exercisementioning
confidence: 81%
“…POGGI et al [31] demonstrated that arm elevation signifi cantly increased inspiratory muscle work in COPD patients with chronic respiratory failure and that NIV during arm elevation reduced dynamic intrinsic positive end expiratory pressure (PEEPi) and inspiratory muscle work while increasing minute ventilation. In a heterogeneous group of patients with chronic hypercapnic respiratory failure enrolled in an acute randomised crossover trial, NIV during unsupported arm exercise increased endurance time, reduced dyspnoea and perceived exertion and improved oxygenation compared with exercise without NIV [32]. In this study, supplemental oxygen was added during exercise testing to maintain arterial oxygen saturation measured by pulse oximetry (Sp,O 2 ) at ~93% at rest.…”
Section: Lower-limb Exercisementioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, it has been reported that in chronic hypercapnic COPD under long-term ventilatory support, NIV can also be administered during walking, resulting in improved oxygenation, decreased dyspnoea and increased walking distance. Therefore, NIV during walking could prevent hypoxia-induced complications [120,121]. Nocturnal NIV has been suggested as an addition to diurnal pulmonary rehabilitation in COPD patients [122,123].…”
Section: Rehabilitationmentioning
confidence: 99%